2012
DOI: 10.2337/dc11-1491
|View full text |Cite
|
Sign up to set email alerts
|

Novel Urinary Protein Biomarkers Predicting the Development of Microalbuminuria and Renal Function Decline in Type 1 Diabetes

Abstract: OBJECTIVETo define a panel of novel protein biomarkers of renal disease.RESEARCH DESIGN AND METHODSAdults with type 1 diabetes in the Coronary Artery Calcification in Type 1 Diabetes study who were initially free of renal complications (n = 465) were followed for development of micro- or macroalbuminuria (MA) and early renal function decline (ERFD, annual decline in estimated glomerular filtration rate of ≥3.3%). The label-free proteomic discovery phase was conducted in 13 patients who progressed to MA by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 40 publications
0
38
0
1
Order By: Relevance
“…Seven proteins were measured simultaneously by selected reaction monitoring (SRM) in the baseline sample. The proteins were chosen because they increased in the discovery proteomic analysis (haptoglobin, angiotensinogen, agrin and mannan-binding lectin serine protease 2), decreased in the proteomic analysis (LAMP-2) or were shown to increase in diabetic nephropathy in the literature (NGAL [2628] and uromodulin [29]). Haptoglobin was able to discriminate between groups in this verification study but agrin was not (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Seven proteins were measured simultaneously by selected reaction monitoring (SRM) in the baseline sample. The proteins were chosen because they increased in the discovery proteomic analysis (haptoglobin, angiotensinogen, agrin and mannan-binding lectin serine protease 2), decreased in the proteomic analysis (LAMP-2) or were shown to increase in diabetic nephropathy in the literature (NGAL [2628] and uromodulin [29]). Haptoglobin was able to discriminate between groups in this verification study but agrin was not (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Last, we used a commercially available ELISA, which has been evaluated in prior studies of clinical outcomes, to assay uromodulin in our study. 14,33-35 …”
Section: Discussionmentioning
confidence: 99%
“…Our results concur with the postulated function of apoJ as a part of the quality control system for preventing the accumulation of protein aggregates (4). apoJ expression increases during various physiologic and pathologic stresses (44, 4648), and its binding to client proteins in blood, such as albumin, fibrinogen, or ceruloplasmin, is promoted after inducing shear stress in plasma (6). In the context of cardiovascular disease, a number of studies have reported different protective effects of apoJ (49).…”
Section: Discussionmentioning
confidence: 99%